2022
DOI: 10.1007/s12010-022-03959-9
|View full text |Cite
|
Sign up to set email alerts
|

Promising Endophytic Alternaria alternata from Leaves of Ziziphus spina-christi: Phytochemical Analyses, Antimicrobial and Antioxidant Activities

Abstract: Fungal endophytes are considered one of the most important reservoirs of bioactive compounds which defeat resistant microbes. In our study, endophytic Alternaria alternata was isolated from Ziziphus spina-christi and identified morphologically and genetically with accession number OM 331,682. Preliminary phytochemical screening of ethyl acetate (EA) crude extract of A. alternata revealed that this extract contains alkaloids, tannins, flavonoids, glycosides, phenols, and terpenoids. Moreover, the extract was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 72 publications
0
18
0
1
Order By: Relevance
“…The recorded scavenging activity of the aqueous methanolic extracts of T. ammi, F. assa-foetida, E.cardamomum1, S. alexandrina, A. obesum, E.cardamomum2, T. when ascorbic acid is used as standard [31]. Alternaria alternata that had been isolated from Ziziphus spina-christi reported to have as potential antioxidant activity against DPPH as the IC 50 reached 409µg/ml [32]. Our finding that T. ammi seed extract has a strong ABTS scavenging activity as the IC 50 reached 100.035 ± 19.38µg is in full agreement with the report that studied 24 commonly used medicinal plants from Nepal and Japan and stated that T. ammi seed showed a strong activity against DPPH as the recorded % of inhibition was 90.67 ± 0.58 [33].…”
Section: Resultsmentioning
confidence: 99%
“…The recorded scavenging activity of the aqueous methanolic extracts of T. ammi, F. assa-foetida, E.cardamomum1, S. alexandrina, A. obesum, E.cardamomum2, T. when ascorbic acid is used as standard [31]. Alternaria alternata that had been isolated from Ziziphus spina-christi reported to have as potential antioxidant activity against DPPH as the IC 50 reached 409µg/ml [32]. Our finding that T. ammi seed extract has a strong ABTS scavenging activity as the IC 50 reached 100.035 ± 19.38µg is in full agreement with the report that studied 24 commonly used medicinal plants from Nepal and Japan and stated that T. ammi seed showed a strong activity against DPPH as the recorded % of inhibition was 90.67 ± 0.58 [33].…”
Section: Resultsmentioning
confidence: 99%
“… 33 Additionally, Zizyphus Spina has endophytic A. Alternaria, which has potent antioxidant activity that can cause cell membrane disruption. 34 Finally, the tannins in Zizyphus Spina, by eliminating Iron, reduce the pathogen growth and proliferation. 35 …”
Section: Discussionmentioning
confidence: 99%
“…33 Additionally, Zizyphus Spina has endophytic A. Alternaria, which has potent antioxidant activity that can cause cell membrane disruption. 34 Finally, the tannins in Zizyphus Spina, by eliminating Iron, reduce the pathogen growth and proliferation. In a study by Butassi et al 36 it was reported that Phytolacca tetramera from Argentina has antifungal activity against Candida albicans and Candida glabrata.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence is showing that plants with antimicrobial activities may provide the most viable opportunity to screen out novel fungal endophytes with bioactive compounds ( Strobel et al, 2004 ; Lv et al, 2010 ; Cui et al, 2015 ; Malhadas et al, 2017 ). For example, the endophytic A. alternata isolated from the leaves of the medicinal plant Ziziphus spina-christi displayed positive inhibition activity against several pathogenic bacteria and fungi ( Elghaffar et al, 2022 ). Similarly, endophytic fungi isolated from many plants, i.e., Dysosma versipellis , Saussurea involucrate , and Rhododendron tomentosum ( Lv et al, 2010 ; Tejesvi et al, 2011 ; Tan et al, 2018 ), with high antimicrobial efficiency also potentially represent new antibacterial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…with antibacterial, antifungal, and anticancer activities ( Hashem et al, 2022 ; Salem et al, 2022b ; Shehabeldine et al, 2022a ). Therefore, endophytic fungi provide the possibility of discovering valuable natural drugs with novel structures and biological activities ( Elghaffar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%